TOWARDS DEVELOPMENT AND PROSPERITY (Academia Science Repository, 2023)
As a result of the attention and care of the President of the Republic of Uzbekistan Shavkat Mirziyoyev, the positive results achieved in many areas during the past period have fundamentally changed the living standards of the population.